Effectiveness of vildagliptin versus other oral antidiabetes drugs as add-on to sulphonylurea monotherapy: Post hoc analysis from the EDGE study. Issue 6 (December 2016) - Prasanna Kumar, K.M.; Phadke, U.; Brath, H.; Gawai, A.; Paldánius, P.M.; Mathieu, C.
Highlights: Retrospective data of 3756 patients with T2DM on SU monotherapy. Vildagliptin resulted in better glycaemic control without tolerability issues than other OADs as add-on to SU. Present analysis supports the use of DPP-4 inhibitors for treatment intensification of first-line SU if metformin is not an option. Abstract: Aim: In this post hoc analysis of the EDGE study, we assessed the effectiveness and safety of vildagliptin versus other oral antidiabetes drugs (OADs) as add-on to first-line sulphonylurea (SU) therapy in patients who did not receive metformin in a real-life setting. Methods: The primary endpoint was odds of achieving an HbA1c reduction of >0.3% without tolerability issues. Secondary endpoint was odds of achieving HbA1c <7.0% without hypoglycaemia or weight gain. Changes in HbA1c, body weight; and safety were also assessed. Results: 2936 patients received vildagliptin and 820 received comparator OADs (any α-GI, TZD, glinide) as add-on to first-line SU therapy. Overall, the mean age, disease duration, HbA1c, and BMI at baseline were 57.1 years, 6.3 years, 8.5%, and 27.7 kg/m 2, respectively. The odds ratios for achieving primary and secondary endpoints were 1.6 (95% CI: 1.36, 1.86; p < 0.0001) and 1.8 (1.45, 2.21; p < 0.0001), respectively, in favour of vildagliptin. The between-treatment differences (vildagliptin vs. comparator OAD) for the mean change in HbA1c and body weight were −0.2 ± 0.04% ( p < 0.0001) and −0.8 ± 0.16 kg ( p < 0.0001), respectively. Overall, the incidence of adverse events was low (vildagliptin, 7% vs. comparator, 8.2%) in both groups. Similar results were observed in a subset of patients enrolled from India and patients who received TZDs as a comparator OAD. Conclusion: Under real-life settings, vildagliptin as add-on to SU monotherapy showed better glycaemic response without tolerability issues compared with other OADs.